Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Kebudayaan Dan Pariwisata Kabupaten Toraja Utara - Anggi Utami; Dian Intan Tangkeallo; Helba Rundupadang (Universitas Kristen Indonesia Toraja, 2023)
This study aims to determine the effect of training and work discipline on employee performance at the North Toraja Regency Culture and Tourism Office. And the object in this study is the Culture and Tourism Office of North Toraja Regency. The population in this study were all employees of the culture and tourism service, totaling 58 people. The results of this study indicate that training has no effect on performance and work discipline simultaneously. the coefficient of determination obtained a value of 0.378 or 37.8%.